Activation of aldehyde dehydrogenase 2 protects ethanol‐induced osteonecrosis of the femoral head in rat model. Issue 6 (14th May 2022) - Lin, Xiaoyi; Zhu, Daoming; Wang, Kaiyang; Luo, Pengbo; Rui, Gang; Gao, Youshui; Liu, Fuan; Yu, Hongping
Abstract: Objectives: Osteonecrosis of the femoral head (ONFH) is a devastating disease characterized by destructive bone structures, enlarged adipocyte accumulation and impaired vascularization. The aldehyde dehydrogenase 2 (ALDH 2) is the limiting enzyme for ethanol metabolism with many physiological functions. The aim was investigated the potential protective role of activated ALDH 2 by Alda‐1 for ethanol‐induced ONFH. Materials and Methods: The ethanol‐induced ONFH in rat was performed to explore the protective of Alda‐1 by various experimental methods. Subsequently, the effect of Alda‐1 and ethanol on the osteogenic and adipogenic differentiation was investigated via multiple cellular and molecular methods. Finally, the effect of Alda‐1 and ethanol on the neo‐vascularization was detected in Human umbilical vein endothelial cells (HUVECs) and ONFH model. Results: Firstly, radiographical and pathological measurements indicated that alda‐1 protected ethanol‐induced ONFH. Moreover, ethanol significantly inhibited the proliferation and osteogenic differentiation of BMSCs, whereas Alda‐1 could distinctly rescue it by PI3K/AKT signalling. Secondly, ethanol remarkably promoted the lipid vacuoles formation of BMSCs, while Alda‐1 significantly retarded it on BMSCs by AMPK signalling pathway. Finally, ethanol significantly inhibited proliferation and growth factor level resulting in reduced angiogenesis, whereas Alda‐1 could rescue the effect of ethanol. Additionally, Alda‐1 significantly reduced the occurrence of ONFH and promoted vessel number and distribution in alcoholic ONFH. Conclusions: Alda‐1 activation of ALDH 2 was highly demonstrated to protect ethanol‐induced ONFH by triggering new bone formation, reducing adipogenesis and stimulating vascularization. Abstract : Alda‐1 activation of ALDH 2 was highly demonstrated to protect ethanol‐induced ONFH by triggering new bone formation, reducing adipogenesis and stimulating vascularization. Therefore, ALDH 2 may be a potential therapeutic target and small molecule Alda‐1 may be promising pharmacotherapeutic for ONFH in the future.